2019
DOI: 10.3171/2018.5.jns18140
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous infusion of mesenchymal stem cells promotes functional recovery in a rat model of chronic cerebral infarction

Abstract: OBJECTIVEIntravenous infusion of mesenchymal stem cells (MSCs) derived from adult bone marrow improves behavioral function in rat models of cerebral infarction. Although clinical studies are ongoing, most studies have focused on the acute or subacute phase of stroke. In the present study, MSCs derived from bone marrow of rats were intravenously infused 8 weeks after the induction of a middle cerebral artery occlusion (MCAO) to investigate whether delayed systemic injection of MSCs improves functional outcome i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…These effects were potentially mediated via an adenosine monophosphate-activated protein kinase (AMPK)-dependent intercellular adhesion molecule-1 (ICAM-1) downregulation. Recently, Namioka et al provided evidence that intravenous infusion of BMSCs at 8 weeks after MCAO stabilized the BBB, reduced microvascular leakage and improved behavior function, which indicated that BMSCs could exert functional benefits even in the chronic phase of ischemic stroke [ 59 ].…”
Section: Effects Of Cell Therapy On Bbb Integrity After Ischemic Strokementioning
confidence: 99%
“…These effects were potentially mediated via an adenosine monophosphate-activated protein kinase (AMPK)-dependent intercellular adhesion molecule-1 (ICAM-1) downregulation. Recently, Namioka et al provided evidence that intravenous infusion of BMSCs at 8 weeks after MCAO stabilized the BBB, reduced microvascular leakage and improved behavior function, which indicated that BMSCs could exert functional benefits even in the chronic phase of ischemic stroke [ 59 ].…”
Section: Effects Of Cell Therapy On Bbb Integrity After Ischemic Strokementioning
confidence: 99%
“…[ 3–6 ] In different animal stroke models, MSC treatment demonstrated increased axonal density and remodeling around the ischemic lesions [ 7–9 ] and was correlated with improved functional recovery. [ 10–15 ] The therapeutic effects of MSC transplantation could be attributed to the secretion of factors that promote axonal growth and neurogenesis. [ 16 ] Recently, Nagahama et al.…”
Section: Experimental Attempts To Use Mesenchymal Stem Cells In the Tmentioning
confidence: 99%
“…have shown that IV injection of MSCs enhanced cortical connections through the corpus callosum and enhanced the expression of synaptophysin in ipsilateral neurons in a rat model of cerebral infarction. [ 14 ]…”
Section: Experimental Attempts To Use Mesenchymal Stem Cells In the Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al demonstrated that MSCs induced decline of the tight junction proteins degradation, as well as increased expression of CD31 and pericyte density in the NVU after intravenous administration to rats [ 67 ]. Chung et al [ 68 ] has also shown that systemic administration of MSCs into rats provides a protective effect against hippocampal neuronal death due to reduction of endothelial damage and neutrophil infiltration. Moreover, after IV infusion of MSCs in the model of small vessel disease in stroke-prone spontaneously hypertensive rats, Nakazaki et al [ 69 ] observed restoration of BBB function via activation of both transforming growth factor-β and angiopoietin 1 signaling pathways, leading to remodeling of the microvasculature.…”
Section: Blood–brain Barrier In Stroke and Its Response To Msc Transplantationmentioning
confidence: 99%